Os incentivos à produção, seus efeitos na segurança e na saúde do trabalho e entre coletivos de trabalho: uma abordagem da formação em ergonomia - Pamela Astudillo; Carlos Ibarra (Universidade do Porto, 2019)
Chile has suffered a precarization of employment since the 1980s, exacerbating a neoliberal economic model and labor reforms that have introduced new forms of work, called atypical, with remuneration mechanisms based on the deal, with collective or individual wage incentives. The mechanisms of representation in companies have been insufficient to improve employment conditions and even less to reflect on how these can influence the health of workers. In addition, union action has been decreasing in this area. This context has discouraged collective work and cooperation among workers. This article aims to show that ergonomics training contributes to union leaders and OSH inspectors a practical knowledge about the impacts on the activity and OSH, among the collectives of work and the consequences for cooperation that have changes in the organization of work and incentive mechanisms salary.